PENGARUH PEMBERIAN PUPUK DAUN CAIR TERHADAP INTENSITAS SERANGAN Tobacco Mosaic Virus (TMV), PERTUMBUHAN, DAN PRODUKSI TANAMAN TEMBAKAU (Nicotiana tabacum L.) - Rois Hanadyo; Tutung Hadiastono; Mintarto Martosudiro (Jurnal HPT (Hama Penyakit Tumbuhan), 2013)
ABSTRACTVirginia tobacco (Nicotiana tabacum L.) is an industrial plant with a fairly higheconomic value in Indonesia. One constraint of t tobacco cultivation is a disorderdiseases such as mosaic disease that caused by Tobacco Mosaic Virus that canreduce yields and degrade leaf tobacco (Semangun, 1996). One effort to produce a healthy business is tobacco fertilization. The dose and ratio of NPK fertilizer can squeeze vulnerability and increase the resilience of crops to diseases, especially diseases of TMV in tobacco. Implementation of the research began in January- May 2012 in the greenhouse and the laboratory of plant pathology, Faculty of Agriculture University of Brawijaya Malang. The research was carried out using a complete randomized design (RAL) are composed of two factors with treatment 4 concentration (0%, 0,3%, 0,5%, 1%), and 3 the number of the application (1x, 2x, 5x). Each treatment was repeated three times. From all leaf fertilizer application and the amount of leaf fertilizer liquid, the concentration ratio of 0.3% with 2x the number of applications on a 7 day time interval indicates the weight of wet leaves on the highest of 95,467 grams of dried leaves with weights of 11,430 grams.Key words : Virginia tobacco, Tobacco Mosaic Virus, Leaf fertilizer liquid